Optimized Sample Adaptive Offset Filter in HEVC - N. Archana; R. Menaka; P. T. Vasanth Raj; G. Keerthivasan; N. Kumar (Advances in Multimedia)
The high-efficiency video coding (HEVC) standard incorporates sample adaptive offset (SAO) as an in-loop filtering technique to reduce distortion. The fundamental tenet of SAO is to classify every reconstructed pixel and then simply add the offset to each group of pixels. The previous existing technique employs 32 bands in band offset (BO) calculation to determine the proper offset value to minimize the distortion in the SAO estimate algorithm for statistics collection and parametric determination procedure. The suggested method will reduce the necessary band count by 16 bands. It does not alter how edge offset is determined in any way. It offers enough and efficient room for creating superior band group predictions and selections, as well as an ideal decrease in the implemented area. Thus, reducing the number of bands to 16 also decreases the amount of storage needed to hold each pixel’s information in binary files by up to 0.65%.